PEMANFAATAN LIMBAH TALAS (Xanthosoma sagittifolium L) UNTUK PEMBUATAN PUPUK BOKASIH DENGAN BIOAKTIVATOR Effective Microorganism (EM-4) - Yuanita; Daryono (JURNAL AGRIMENT, 2019)
Taro plants are plants that grow faster and grow in areas that are runny and moist. These taro plants are used to make flour, chips and traditional food, while the leaves and stems for animal feed are like pigs and can be used as ingredients for making bokashi fertilizer. EM-4 bioactivator is a material that contains several microorganisms and helps speed up the composting process.The purpose of this study was to determine the time needed to make bokashi fertilizer using an EM-4 bioactivator and analyze nutrients N, P, K, C, C / N and pH. This research was conducted at the Samarinda State Polytechnic Production Laboratory.The results of the study on the Utilization of Taro Waste (Xanthosoma Sagittifolium L) for Making Bokasih Fertilizer By Adding Effectve Microorganisms (Em-4), it can be seen that bokashi fertilizer is processed so on day 15 of 120 kg raw material becomes 30 kg and by observation temperature 28 ° C, pH 7, blackish brown color and odorless. Total P analysis: 3.3709, total K: 3.2954, total N: 0.8680, C Total: 5.6996, C / N: 6.5595